Sustainable Development Building With The Analytical Approach of Blue Economic And Food Security - Wenny Desty Febrian; Indra Sani; Siti Annisa Wahdiniawat; Ari Apriani; Evaf Maulina (ABNUS Publisher, 2023)
The blue economy refers to economic activities focused on advanced sustainable management and conservation of marine and coastal resources and sustainable development to promote economic growth. The challenge of meeting the food needs of a growing global population requires sustainable food supply chains anchored in coastal communities and sustainable food production. In addition, marine resources are critical to ensuring food security, accounting for two-thirds of total global fish production, 80% of global aquaculture production, and the per capita supply of fish is 65% higher than the world average. As the world's population grows, the amount of food needed in the future will depend on intrinsic factors and human choices. This chapter examines the current state of marine resources and proposes several steps forward based on the opportunities and challenges that exist through the use of secondary data to accelerate the sustainable use of marine resources and a partial analysis of the human actions that shape to the sustainable future, simulate, supply chain, and food waste